Antibacterial Activity of Endophytic Fungi from Bidara Roots Against Bacteria that Cause Skin Infections - Nurdayani, Sitti; Fitriana, Fitriana; Amirah, Sitti (Journal Microbiology Science, 2024)
Endophytic fungi are fungi that grow and colonize plant tissues and are capable of producing bioactive compounds similar to those produced by their host. This study aims to determine the concentration of endophytic fungal isolates from Bidara roots (Ziziphus mauritiana Lam) that have antibacterial activity against bacteria that cause skin infections using the agar diffusion method. The research method begins with the rejuvenation of IFAZ-6 isolates, and microscopic and macroscopic observations are carried out. The isolates were fermented using Maltose Yeast Broth medium at 200 rpm for 21 days. The fermentate was extracted with an ethyl acetate solvent to obtain a thick extract. The tests carried out were minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and antibacterial activity tests carried out using the agar diffusion method. The results of the antibacterial activity test showed that the IFAZ-6 isolate extract at a concentration of 800 ppm showed antibacterial activity against Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Propionibacterium acnes. The statistical analysis results showed that the extract of isolate IFAZ-6 against Staphylococcus aureus and Staphylococcus epidermidis at concentrations of 800-1600 ppm and 1600–3200 ppm exhibited the same antibacterial activity. The bacterium Pseudomonas aeruginosa showed the same antibacterial activity at all tested concentrations, and the bacterium Propionibacterium acnes at concentrations of 1600–3200 ppm also exhibited the same antibacterial activity.